BUSINESS MANAGEMENT AND ENTREPENEURSHIP FOR THE SANTRI AT PESANTREN AR-RAUDHATUL HASANAH MEDAN - Aisyah; Sofiyah, Fivi Rahmatus; Lubis, Yeti Meliany (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
The activity of devotion is done at Pesantren Ar-Raudhatul Hasanah Medan which the participants are santri who manage santri mart and student store, debriefing of finance management and management of business is very important to run business, sometimes important knowledge about entrepreneurship become part of learning process, entrepreneurship santri can better understand in running a business, according to their talents and interests. With training and demonstration patterns students can get information and learning.